Functional Magnetic Stimulation of Inspiratory and Expiratory Muscles in Subjects With Tetraplegia. Issue 7 (9th March 2016) - Zhang, Xiaoming; Plow, Ela; Ranganthan, Vinoth; Huang, Honglian; Schmitt, Melissa; Nemunaitis, Gregory; Kelly, Clay; Frost, Frederick; Lin, Vernon
Abstract: Background: Respiratory complications are major causes of morbidity and mortality in persons with a spinal cord injury, partly because of respiratory muscle paralysis. Earlier investigation has demonstrated that functional magnetic stimulation (FMS) can be used as a noninvasive technology for activating expiratory muscles, thus producing useful expiratory functions (simulated cough) in subjects with spinal cord injury. Objective: To evaluate the effectiveness of FMS for conditioning inspiratory and expiratory muscles in persons with tetraplegia. Design: A prospective before and after trial. Setting: FMS Laboratory, Louis Stokes Cleveland VA Medical Center, Cleveland, OH. Participants: Six persons with tetraplegia. Method: Each subject participated in a 6‐week FMS protocol for conditioning the inspiratory and expiratory muscles. A magnetic stimulator was used with the center of a magnetic coil placed at the C7‐T1 and T9‐T10 spinous processes, respectively. Pulmonary function tests were performed before, during, and after the protocol. Main Outcome Measurements: Respiratory variables included maximal inspiratory pressure (MIP), inspiratory reserve volume (IRV), peak inspiratory flow (PIF), maximal expiratory pressure (MEP), expiratory reserve volume (ERV), and peak expiratory flow (PEF). Results: After 6 weeks of conditioning, the main outcome measurements (mean ± standard error) were as follows: MIP, 89.6 ± 7.3 cm H2 O; IRV, 1.90 ± 0.34 L; PIF, 302.4 ± 36.3 L/min; MEP, 67.4 ± 11.1 cm H2 O; ERV, 0.40 ± 0.06 L; and PEF, 372.4 ± 31.9 L/min. These values corresponded to 117%, 107%, 136%, 109%, 130%, and 124% of pre‐FMS conditioning values, respectively. Significant improvements were observed in MIP ( P = .022), PIF ( P = .0001), and PEF ( P = .0006), respectively. When FMS was discontinued for 4 weeks, these values showed decreases from their values at the end of the conditioning protocol, which suggests that continual FMS may be necessary to maintain improved respiratory functions. Conclusion: FMS conditioning of the inspiratory and expiratory muscles improved voluntary inspiratory and expiratory functions. FMS may be a noninvasive technology for respiratory muscle training in persons with tetraplegia.